The protein deficit myth - Ricardo Abramovay; Nadine Marques Nunes-Galbes; Fernanda Helena Marrocos-Leite; Eduardo Augusto Fernandes Nilson; Maria Laura da Costa Louzada (Revista de Saúde Pública)
ABSTRACT Epidemiological data shows that the consumption of animal-based foods in high-income countries is excessive and harmful to health. But the association between poverty and protein deficiency is frequent, both in scientific literature and in the documents of multilateral organizations. There is a conceptual trap in this link, which consists of focusing on one nutrient and not on the whole dietary pattern. In 1974, in a text that has become a classic of nutrition science, Donald McLaren has already highlighted the mistake made by multilateral development organizations in focusing their efforts on protein supply—often in industrialized forms—without considering that, in most cases, once energy needs are met, protein deficiency is unlikely to occur. Data from the 2017–2018 Consumer Expenditure Survey helps to dispel this myth: even among the poorest 20% of the Brazilian population, the proportion of those with insufficient protein intake is tiny.